2014
DOI: 10.1177/0961203314527367
|View full text |Cite
|
Sign up to set email alerts
|

Chronic active Epstein-Barr virus infection mimicking autoimmune hepatitis exacerbation in a patient with systemic lupus erythematosus

Abstract: Chronic active Epstein-Barr virus infection (CAEBV) is characterized by chronic infectious mononucleosis-like symptoms. We report a very rare case with autoimmune hepatitis (AIH) complicated by CAEBV. A 50-year-old woman with systemic lupus erythematosus (SLE) complicated by AIH began to suffer from acute respiratory failure and her clinical symptoms improved rapidly in response to steroid treatment. However, during the gradual tapering of the steroid dose, a steady increase of the serum hepatobiliary enzyme l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…In particular, among autoimmune diseases, the development of systemic lupus erythematosus (SLE) has been correlated with EBV re-activation (as well as with several other causative infections) [76][77][78][79][80][81][82]. SLE is an autoimmune chronic inflammatory disease, usually characterized by injury to the skin, joints, kidneys, nervous system, and mucous membranes.…”
Section: When It Rains It Pours: the Case Of Vh4-34 Germlinementioning
confidence: 99%
“…In particular, among autoimmune diseases, the development of systemic lupus erythematosus (SLE) has been correlated with EBV re-activation (as well as with several other causative infections) [76][77][78][79][80][81][82]. SLE is an autoimmune chronic inflammatory disease, usually characterized by injury to the skin, joints, kidneys, nervous system, and mucous membranes.…”
Section: When It Rains It Pours: the Case Of Vh4-34 Germlinementioning
confidence: 99%
“…Although there is a report of AIH being induced in a patient with preexisting CAEBV and successfully treated with a corticosteroid,31 CAEBV is generally a life-threatening progressive disease if adequate management is neglected. In some cases of CAEBV, the clinical, laboratory, and histological features are quite similar to those of AIH, but the prognosis is extremely poor 32,33. CAEBV should be included in the differential diagnosis of patients who do not respond sufficiently to immunosuppressive therapy.…”
Section: Pitfalls In the Diagnosis Of Classical Aihmentioning
confidence: 99%
“…Numerous studies confirmed higher frequencies and elevated titres of EBV-directed antibodies, against lytic cycle antigens, in SLE patients compared to healthy controls (HCs), indicating frequent EBV reactivations (reviewed in [11,18] The decreased control of EBV in SLE patients was also lately demonstrated by the presence of EBV DNA detected by PCR in serum from SLE patients [26], and by several case reports. A 50-year-old woman diagnosed with SLE (and concurrent autoimmune hepatitis) developed chronic active EBV infection with EBER-positive lymphocytes found in both liver and gastric mucosal biopsies and in high concentrations in the CD4+ T-cells in the blood [27]. Similarly, an 86-year-old woman with SLE developed a rare form of EBVpositive plasmablastic lymphoma in the colon [28].…”
Section: Ebv In Slementioning
confidence: 99%